The association between individual attachment patterns, the perceived social support, and the psychological well-being of Turkish informal caregivers - BEKİROĞLU, GÜLNAZ NURAL; KUŞCU, MEHMET KEMAL (WILEY, 2009)
Background: This study aimed to investigate the relations among the psychological well-being (i.e. depression and state/trait anxiety levels), attachment patterns (i.e. secure, ambivalent, avoidant), and the perceived social support from family/friends/significant others of caregivers of cancer patients in Turkey. Methods: Fifty-one caregivers of adult cancer patients were recruited from the oncology outpatient clinic of the Marmara Medical School Hospital in Istanbul. Caregivers were assessed with the Adult Attachment Scale, the Beck Depression Inventory, State-trait Anxiety Inventories, and the Multidimensional Scale of Perceived Social Support. Results: Stepwise multiple regression analysis indicated that depression was predicted by ambivalent attachment and the perceived social support from family. The support from significant others was the significant predictor of trait anxiety and the caregivers' ambivalent attachment score was the significant predictor of state anxiety. Conclusions: We assert that ambivalent attachment pattern could confer a vulnerability to psychological distress in cancer caregivers. Assessing the psychological experiences and needs of caregivers and being aware of possible risk factors (such as attachment patterns) and protective factors (social support network) for depression and anxiety might be helpful for successful programmes and interventions that support the caregivers of cancer patients. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: informal caregivers; cancer; oncology; depression; attachment; perceived support; ADULT ATTACHMENT; CANCER-PATIENTS; INTIMATE-RELATIONSHIPS; PSYCHOPATHOLOGY; PARTNERS; STYLES; BURDEN; IMPACT; EXPERIENCES; DEPRESSION